Development Of An Immune Tuberculosis Antibody Library: Monoclonal Antibody Generation For a-Crystalline Antigen - Hamidon, Nurul Hamizah (2017)
Antibodies are very important for therapeutic and diagnostic applications for infectious diseases. Immune libraries are useful for infectious disease applications because it would allow for better and selective enrichment of antibodies against disease antigens. The generations of antibody libraries are necessary to produce the monoclonal antibodies. Immune scFv antibody library was generated from six donors (tuberculosis patients). Conventional PCR method was used to amplify all possible antibody genes, which were then cloned into the pLABEL, phagemid vector. A two-step cloning procedure was done to generate the antibody library. The library size of the mini HC library and the scFv library constructed was approximately around 107 and 109 individual clones respectively.